Live Monitoring and Analysis of Fungal Growth, Viability, and Mycelial Morphology Using the IncuCyte NeuroTrack Processing Module - Sebastian Wurster (American Society for Microbiology, 2019)
ABSTRACT Efficient live-imaging methods are pivotal to understand fungal morphogenesis, especially as it relates to interactions with host immune cells and mechanisms of antifungal drugs. Due to the notable similarities in growth patterns of neuronal cells and mycelial networks, we sought to repurpose the NeuroTrack (NT) processing module of the IncuCyte time-lapse microscopy system as a tool to quantify mycelial growth and branching of pathogenic fungi. We showed the robustness of NT analysis to study Candida albicans and five different molds and confirmed established characteristics of mycelial growth kinetics. We also documented high intra- and interassay reproducibility of the NT module for a spectrum of spore inocula and culture periods. Using GFP-expressing Aspergillus fumigatus and Rhizopus arrhizus, the feasibility of fluorescence-based NT analysis was validated. In addition, we performed proof-of-concept experiments of NT analysis for several translational applications such as studying the morphogenesis of a filamentation-defective C. albicans mutant, the effects of different classes of antifungals (polyenes, azoles, and echinocandins), and coculture with host immune cells. High accuracy was found, even at high immune cell-to-fungus ratios or in the presence of fungal debris. For antifungal efficacy studies, addition of a cytotoxicity dye further refined IncuCyte-based analysis, facilitating real-time determination of fungistatic and fungicidal activity in a single assay. Complementing conventional MIC-based assays, NT analysis is an appealing method to study fungal morphogenesis and viability in the context of antifungal compound screening and evaluation of novel immune therapeutics. IMPORTANCE Pathogenic fungi remain a major cause of infectious complications in immunocompromised patients. Microscopic techniques are crucial for our understanding of fungal biology, host-pathogen interaction, and the pleiotropic effects of antifungal drugs on fungal cell growth and morphogenesis. Taking advantage of the morphological similarities of neuronal cell networks and mycelial growth patterns, we employed the IncuCyte time-lapse microscopy system and its NeuroTrack image analysis software package to study growth and branching of a variety of pathogenic yeasts and molds. Using optimized image processing definitions, we validated IncuCyte NeuroTrack analysis as a reliable and efficient tool for translational applications such as antifungal efficacy evaluation and coculture with host immune effector cells. Hence, the IncuCyte system and its NeuroTrack module provide an appealing platform for efficient in vitro studies of antifungal compounds and immunotherapeutic strategies in medical mycology.